Lipid composition and dynamics of cell membranes of Bacillus stearothermophilus adapted to amiodarone - Rosa, Sónia M. L. J. (2000)
Bacillus stearothermophilus, a useful model to evaluate membrane interactions of lipophilic drugs, adapts to the presence of amiodarone in the growth medium. Drug concentrations in the range of 1-2 [mu]M depress growth and 3 [mu]M completely suppresses growth. Adaptation to the presence of amiodarone is reflected in lipid composition changes either in the phospholipid classes or in the acyl chain moieties. Significant changes are observed at 2 [mu]M and expressed by a decrease of phosphatidylethanolamine (relative decrease of 23.3%) and phosphatidylglycerol (17.9%) and by the increase of phosphoglycolipid (162%). The changes in phospholipid acyl chains are expressed by a decrease of straight-chain saturated fatty acids (relative decrease of 12.2%) and anteiso-acids (22%) with a parallel increase of the iso-acids (9.8%). Consequently, the ratio straight-chain/branched iso-chain fatty acids decreases from 0.38 (control cultures) to 0.30 (cultures adapted to 2 [mu]M amiodarone). The physical consequences of the lipid composition changes induced by the drug were studied by fluorescence polarization of diphenylhexatriene and diphenylhexatriene-propionic acid, and by differential scanning calorimetry. The thermotropic profiles of polar lipid dispersions of amiodarone-adapted cells are more similar to control cultures (without amiodarone) than those resulting from a direct interaction of the drug with lipids, i.e., when amiodarone was added directly to liposome suspensions. It is suggested that lipid composition changes promoted by amiodarone occur as adaptations to drug tolerance, providing the membrane with physico-chemical properties compatible with membrane function, counteracting the effects of the drug.